Penerapan Pemrosesan Citra Satelit MODIS Menggunakan Perangkat Lunak SeaDAS untuk Menganalisis Distribusi Klorofil-a di Perairan Aceh Sebelum dan Sesudah Pandemi COVID-19 - Mirna Ria Andini (Jurnal Inotera, 2026)
Chlorophyll-a is an important oceanographic parameter that reflects the level of primary productivity in the waters and the abundance of phytoplankton as the primary producers in the marine food chain. This study aims to analyze a comparison of chlorophyll-a distribution based on Aqua MODIS and Terra MODIS data in the waters off Aceh during the periods before and after the COVID-19 pandemic.The data used were MODIS Level-3 chlorophyll-a data for the period July–December 2019, representing pre-pandemic conditions, and for the period January–June 2023, representing post-COVID-19 pandemic conditions. Data processing was performed using SeaDAS software version 7.3.2 through the stages of preprocessing, cropping, land masking, visualization, and descriptive statistical extraction, which included the minimum, maximum, and average chlorophyll-a concentrations. Further analysis was conducted using Microsoft Excel to generate graphs and comparison tables for the four data sets. The results of the study show that chlorophyll-a concentrations tend to be higher in coastal areas than in offshore waters, indicating a high supply of nutrients from land via river runoff and water mass mixing processes. The average Aqua MODIS chlorophyll-a concentration decreased from 0.3169 mg/m³ in 2019 to 0.2148 mg/m³ in 2023, while Terra MODIS showed a decrease from 0.3076 mg/m³ to 0.2411 mg/m³ over the same period. The decline in chlorophyll-a concentrations following the COVID-19 pandemic indicates changes in primary productivity in the waters, influenced by oceanographic dynamics such as sea surface temperature, current patterns, monsoon winds, and nutrient distribution. Although there were differences in concentration values between the two sensors due to variations in satellite overpass times and atmospheric conditions at the time of recording, both sensors produced relatively consistent spatial distribution patterns. The results of this study are expected to serve as a reference for the management of marine and fishery resources using remote sensing technology in the waters of Aceh.